THE ROLE OF QURAN READING HABIT STRATEGIES IN FACILITATING MEMORIZATION PROCESS FOR STUDENTS IN THE TAHFIDZ CLASS AT MINU SUNAN AMPEL 1 - Siti Khofsah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study discusses the role of the strategy of habitual reading of the Qur'an in facilitating the memorization process in Tahfidz class students at MINU Sunan Ampel 1. The strategy of habitual reading consistently and repeatedly is believed to form a strong memorization pattern, making it easier for students to remember and repeat the verses of the Qur'an. The habit of reading at MINU Sunan Ampel 1 is implemented routinely as part of students' daily activities, accompanied by supporting methods such as takrir and muroja'ah which increase the focus and accuracy of memorization. The main supporting factors for the success of this strategy include student consistency, teacher guidance, and a conducive learning environment. The results of the study indicate that the habit of reading the Qur'an regularly can improve the quality and fluency of students' memorization, thereby significantly facilitating the tahfidz process. Thus, the strategy of habituating reading the Qur'an is an effective approach in learning tahfidz at MINU Sunan Ampel 1.